Exploring clinical characteristics, gender differences, and initial outcomes of a pilot study of the attempted suicide short intervention program (ASSIP) in a Swedish cohort of suicide attempters - Sara Lindström; Johanna Clausen Ekefjärd; Jonas Berge; Marie Dahlin; Anja Gysin-Maillart; Anna Ehnvall; Bo Runeson; Margda Waern; Åsa Westrin (Cogent Psychology)
The Attempted Suicide Short Intervention Program (ASSIP) is a brief therapy aimed at preventing repeat suicide attempts by addressing the underlying backgrounds and vulnerabilities associated with suicidal behaviour. In Switzerland, ASSIP demonstrated an 80% reduction in long-term risk of repeat suicide attempts, but a description of the implementation and effects in a Swedish context is lacking. This pilot study, as part of a larger feasibility study preparing for a future RCT, examines the clinical characteristics of individuals receiving ASSIP in Sweden, focusing on gender differences and initial outcomes. One hundred individuals who had attempted suicide were recruited from psychiatric facilities across Sweden. Demographic and clinical data were collected, including diagnostic information and details about suicide attempt methods. Suicidal intent at index suicide attempt was assessed by the Suicide Intent Scale (SIS). Attitude towards suicide, suicide ideation and behaviour and other suicide-related symptoms were measured using the Suicide Assessment Scale Self-rate (SUAS-S) at baseline and after three sessions of ASSIP, and changes in SUAS-S scores were used to assess initial outcomes. Almost half of the cohort had a mood disorder and 39% had an anxiety disorder. Men were more likely than women to use violent methods in their suicide attempts. The mean SIS score was 17.6. SUAS-S scores had decreased significantly by the third session. The findings of this pilot study showed reduced self-rated scores on SUAS among high-risk individuals after three sessions of ASSIP treatment, suggesting the potential relevance brief, targeted interventions in suicide prevention. Except for the attempt method, no gender differences were found.